Adherence to Environmental Regulation in the European Union Common Agricultural Policy: Social Representations and Conditionality among French Farmers. Issue 3 (27th October 2020) - Gaymard, Sandrine; Goujon, Boris; Lefebvre, Marianne
Abstract: Support for the agricultural sector from the European Union via the Common Agricultural Policy (CAP) is evolving. The last CAP reform in 2014 made one further step toward mandatory approaches. To understand the "social thinking" and behavior when faced with these measures, an innovative application has been adopted. Globally, the farmers' discourse manifests contradictions between environmental concern and the financial dimension, which is the expression of their daily difficulties. Mandatory approaches to sustainable agriculture may favor what the Theory of Conditionality called "legitimate transgressions" if regulations appear unadapted to real practices because compliance and opportunity costs are too high.